Successful percutaneous angioembolisation of bleeding jejunal varix by acrylate glue and coils. (24th October 2013) - Haq, Tanveer Ul; AlQamari, Nauman; Sayani, Raza; Hilal, Kiran
Abstract : Portal hypertension is a common disease worldwide. One of its rare complications is bleeding jejunal varices which is usually asymptomatic and may present with gastrointestinal bleeding. We present a case of a jejunal bleeding that was successfully embolised with acrylate glue and embolisation coils. A middle-aged woman with a history of multiple abdominal surgeries for adenocarcinoma of right ovary, presented to us with multiple episodes of haematochezia. On a CT scan of the abdomen, she was diagnosed with chronic liver disease with portal hypertension, multiple varices at porto-systemic anastomosis and ectopic jejunal varix. She was treated by interventional radiologists by percutaneous embolisation of bleeding varix using glue and embolisation coils through a portal venous approach.